2011
DOI: 10.1111/j.1532-950x.2011.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Transcutaneous Amputation Prosthesis (ITAP) for Limb Salvage in 4 Dogs

Abstract: Implantation of ITAP to the distal limb of dogs is feasible and can result in favorable functional outcomes. Biological integration of osseous and dermal tissues with ITAP is reliable and robust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 52 publications
1
73
0
4
Order By: Relevance
“…The ITAP system: http://www.itap-prosthetics.com/ was designed for a one‐step implantation procedure (see Table ) . It was reported to be applied to one transhumeral amputee, to the human thumb and index finger in one human patient and to four dogs. The approach for the system design is rooted in analysis of special biological structures such as horns, hair, feathers, fingernails, hooves, teeth, and antlers as examples where nature has solved the problems of “percutaneous devices.” As a result, the ITAP system emulates antlers: a flange caps the residuum, and is perforated by twenty‐four 0.7 mm holes are bored immediately below the epithelium to increase dermal attachment …”
Section: Methodsmentioning
confidence: 99%
“…The ITAP system: http://www.itap-prosthetics.com/ was designed for a one‐step implantation procedure (see Table ) . It was reported to be applied to one transhumeral amputee, to the human thumb and index finger in one human patient and to four dogs. The approach for the system design is rooted in analysis of special biological structures such as horns, hair, feathers, fingernails, hooves, teeth, and antlers as examples where nature has solved the problems of “percutaneous devices.” As a result, the ITAP system emulates antlers: a flange caps the residuum, and is perforated by twenty‐four 0.7 mm holes are bored immediately below the epithelium to increase dermal attachment …”
Section: Methodsmentioning
confidence: 99%
“…The implants used here were coated with hydroxyapatite to reduce the risk of implant loosening and to facilitate both osseous and soft‐tissue integration to implants, as previously described in veterinary patients . At 1 year postsurgery, no lucency around the hemipelvic or femoral implants were noted on radiography and CT, consistent with a robust osseointegration of implants.…”
Section: Discussionmentioning
confidence: 97%
“…For example, ongoing animal studies on transcutaneous porous titanium bone implants (Farrell et al, 2014a,b; Fitzpatrick et al, 2011; Pitkin et al, 2009; Shelton et al, 2011) have aimed to reduce skin infection in individuals with bone-anchored lower limb prostheses (Branemark et al, 2014; Drygas et al, 2008; Tillander et al, 2010; Tsikandylakis et al, 2014), and ultimately to improve biomechanics of prosthetic locomotion. It is much less common, however, to translate successful developments in human biomechanics, orthopedic and prosthetic research to veterinary medicine to treat animals with limb loss.…”
Section: Introductionmentioning
confidence: 99%
“…Although few case report studies have suggested that quadrupedal animals might utilize a unilateral distal bone-anchored prosthesis for walking (Farrell et al, 2014a; Fitzpatrick et al, 2011), no studies have been published that rigorously document whether quadrupedal animals systematically utilize unilateral transtibial prostheses during locomotion and how prosthetic locomotion is performed. The use of the prosthetic limb during quadrupedal locomotion might depend on which limb is missing (forelimb versus hindlimb) and on loading demands on the prosthetic limb.…”
Section: Introductionmentioning
confidence: 99%